2021
DOI: 10.18280/ijdne.160214
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Heavy Metals in the Biot of Lake Radoniqi and Badovci, Food Safety: Study of the Natural Environment in the Republic of Kosovo

Abstract: The purpose of this research is to determine the content of heavy metals in the lakes of Kosovo, lakes with heavy metals such as: (Hg, Cd, Pb, As, Fe, Zn, Ni, Cu), in water and water sediment in Lake Radoniq and Lake Badovc. Determination of heavy metals (Pb, Cd, Hg, As), in muscle tissue and fish organs. Parameters as an indicator of fish safety for food, indicator of environmental pollution (Kosovo lake bioten). Age of fish, the amount of fat are important factors that affect the accumulation of heavy metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The soil where the research testing of barley cultivars was done in Peja is reddish brown, while the smonica type soil in Pestovë, which represents almost 25% of Kosovo's soil. In terms of chemical content, based on analyzes performed for research purposes, both field test plots have approximate values,this research presents the findings of the study including the analysis and interpretation of the analyzed data (Dreshaj et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil where the research testing of barley cultivars was done in Peja is reddish brown, while the smonica type soil in Pestovë, which represents almost 25% of Kosovo's soil. In terms of chemical content, based on analyzes performed for research purposes, both field test plots have approximate values,this research presents the findings of the study including the analysis and interpretation of the analyzed data (Dreshaj et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The soil analysis showed that the two researched soils were rich in medium humus, phosphorus, potash, rich in calcium and magnesium, bioaccumulation can be due to bioconcentration (absorption from the food chain), or biomagnification (Dreshaj et al 2021). Based on these data, the doses of nitrogen, phosphorus and potash fertilization were determined, while there was no need for calcium and magnesium fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…The most important source of cadmium in the air is industrial plants. Other sources of anthropogenic origin include phosphate fertilizers (Dreshaj et al, 2021).…”
Section: Introductionmentioning
confidence: 99%